Impact of Psychological and Social Climacteric Changes upon Quality of Life of Middle Age Women in Baghdad City - Muhson, wafaa; Amir, fatin (Iraqi National Journal of Nursing Specialties, 2015)
Objective: to assessthe impact of psychological and social climacteric changes on quality of life among middle age women in Baghdad city Methodology: : A descriptive analytic study was conducted to study the quality of life among middle age women due topsychological and social climacteric changes from February 2013- July 2013. A purposive sampleconsisted of three hundred (300) womenaged (40-65) years who were attending health centers in two sectors in Baghdad / AL- Russafa andAL- karhk . The data were collected through using interview technique , and questionnaire format , which comprises two parts, first part consist (socio-demographic characteristic , the second part quality of life domains (psychological and social domains ) .. The reliability of the questionnaire was determined through a pilot study and, the validity through a panel of (18) experts. Descriptive and inferential statistical analysis procedures were employed for data analysis; all the statistical procedures were tested at P> 0.05 or less . Results:The results show that the climacteric changes for ( psychological domain ) was reported by more than half of study sample which assessed as ( moderate) impact on quality of life .while the assess of social domain ( good). Recommendation:The study recommends for more effort from health care providers to do further researches about the quality of life of middle age women. Moreover, the health care provider should implement an educational program for women about the climacteric changes and how to pass it safely